A NATIONAL STRUGGLE: SENEGALESE WRESTLING AND CASAMANÇAIS SEPARATISM - Deets,Mark W. (2021)
Abstract This paper examines the history of Senegalese wrestling to show how and why separatists from Senegal’s southern Casamance region used distinctions between Senegalese “traditional” wrestling and Casamançais “pure” wrestling to stake a claim to territorial separatism based on claims of cultural separatism. This study of Senegalese wrestling history demonstrates that little about this traditional form of the sport is “traditional.” Rather, the form practiced in Senegalese stadiums today results from changes to earlier forms of the sport practiced in the precolonial era. I argue that although some separatists tried to form these cultural distinctions into a “discourse of grievance” against the Senegalese state, many ordinary Casamançais refused to link their communal cultural identity to the division and violence of separatism.